Penerapan Sistem Presensi Siswa Berbasis NodeMCU ESP8226 (Studi Kasus SMK PGRI Lemahabang Karawang) - Reynaldi Azhar; Yusuf Syamputra; Adhi Rizal (Peneliti.net, 2023)
Presence is an activity of recording attendance data to determine the number of attendees of an agency. In the field of education such as schools, attendance is still done manually which is written in the learning activity book. The impact of the student attendance recapitulation system causes the recapitulation process to be less effective. Therefore, an attendance system is needed in order to improve performance at school in terms of recapitulating student attendance data. The system to be built in this research uses NodeMCU ESP8266 and RFID technology. This research applies SDLC methodology with waterfall model. The stages of the waterfall model that will be carried out are Requirements Analysis, System Design, System Implementation, System Testing, and Documentation. Testing is done using Blackbox and User Acceptance Test. The results of tests conducted using blackbox on hardware and software systems. On the hardware system can be read RFID card as far as 4 cm, and for the software system on all menus show good functionality. For UAT testing using a Likert scale from the results of questionnaires to students getting a percentage value of 80.43% categorized as strongly agreeing on the student attendance system.